Ničnost in zastaranje kondikcijskih zahtevkov - Juhart, Miha (Pravnik, 2024)
The author addresses the issue of limitation of a claim for unjust enrichment arising from the nullity of a contract. The law provides that claims of nullity are not subject to a limitation period. This rule should apply only to the performance of contractual obligations and it should not be extended to claims for unjust enrichment. These claims are subject to limitations according to settled case law. Two pertinent conclusions emerge. Firstly, the decision to pursue a claim for unjust enrichment remains at the discretion of the contracting party. However, this uncertainty as to whether to assert the claim should not persist indefinitely. Therefore, it is proposed that the claim for unjust enrichment be subject to a limitation period. This period should commence from the moment the contracting party becomes aware, or ought to have been aware, that the contract was void and that they possessed a claim. Secondly, nullity does not justify any benefits for either party involved in a void contract. All benefits should be returned, and the party returning the benefit must, in turn, have a claim for the restitution of any contributions it has made.
Keywords: credit agreement; kreditna pogodba; limitation; neopravičena obogatitev; nepošteni pogodbeni pogoji; ničnost; nullity; unfair contract terms; unjust enrichment; zastaranje